Competitive formats and the competitiveness of women’s elite futsal teams: should we follow men’s standards? - Fernando Santos; Duarte Neto; Pedro Neto; Joana Correia; Marta Ferreira; Julia Barreira; Keith Davids (Cogent Social Sciences, 2024)
Greater attention is needed towards creating more equitable performance environments through socially just approaches for athlete development, aligned with developing appropriate sport policies and competitive spaces. Therefore, this study aimed to assess the impact of changes to the competitive format on championship competitiveness and to critically reflect on the use of the men’s competitive models as the guiding factor for changes in women’s sports. Findings showed changes in competitive format were insufficient to increase league competitiveness. Indeed, competitiveness, and inherently, performance development require a more nuanced and ecological understanding of female athlete development. The fact that the highest goal difference per game was found in the season 2022/2023 supports this suggestion, implicating an in-depth analysis around political, social and cultural variables to foster gender equity and actual increases in league competitiveness. Moving forward, there may be the need to consider new possibilities for the competitive format for female futsal athletes and other changes within the sport system that can create a truly equitable environment. Sport policies and competitive spaces within high-performance contexts have a critical role to play in ensuring gender equity and cannot simply imitate male sport.